2016
DOI: 10.1302/2046-3758.52.2000412
|View full text |Cite
|
Sign up to set email alerts
|

Combination of modified mixing technique and low frequency ultrasound to control the elution profile of vancomycin-loaded acrylic bone cement

Abstract: ObjectivesThe objective of this study was to determine if combining variations in mixing technique of antibiotic-impregnated polymethylmethacrylate (PMMA) cement with low frequency ultrasound (LFUS) improves antibiotic elution during the initial high phase (Phase I) and subsequent low phase (Phase II) while not diminishing mechanical strength.MethodsThree batches of vancomycin-loaded PMMA were prepared with different mixing techniques: a standard technique; a delayed technique; and a control without antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 28 publications
(30 reference statements)
4
18
0
Order By: Relevance
“…To ensure good quality and high productivity, engineers tend to prioritize the mixing time with an attempt to minimize it to the greatest degree (Ferraris, 2001). Similar research could be found in other industries related with cementitious materials (Lombois-Burger et al, 2006;Pileggi et al, 2001;Brand et al, 2015;Wendling et al, 2016). The present research describes and assesses the effects of several mixing parameters on the properties of paste materials, such as their fluidity and hardening characteristics.…”
Section: Introductionsupporting
confidence: 59%
“…To ensure good quality and high productivity, engineers tend to prioritize the mixing time with an attempt to minimize it to the greatest degree (Ferraris, 2001). Similar research could be found in other industries related with cementitious materials (Lombois-Burger et al, 2006;Pileggi et al, 2001;Brand et al, 2015;Wendling et al, 2016). The present research describes and assesses the effects of several mixing parameters on the properties of paste materials, such as their fluidity and hardening characteristics.…”
Section: Introductionsupporting
confidence: 59%
“…The results showed that continuous ultrasound increased local T max by 47.6 mg/mL and urinary elimination of vancomycin by 109.56 mg but failed to prolong the local T > MIC. Wendling et al [ 47 ] developed a study to determine the effect of different mixing techniques of vancomycin-impregnated polymethylmethacrylate cement with LFU on antibiotic elution. They found that the combination of a delayed mix technique with LFU treatments could significantly increase both short- and long-term antibiotic elution without affecting mechanical strength.…”
Section: Effect Of Lfu On Antibiotic Release From Implanted Materimentioning
confidence: 99%
“…As the paste backfilling technology has already been a priority option for tailings disposal under policies emphasizing environmental conservation, improper mixing is currently one of the urgent concerns for mining engineers [9,10]. The aim of minimizing the mixing intensity and mixing time without damaging the quality and productivity is widely pursued [11], even in the cementitious materials related industries [12]. Hence, a well-designed mixing technique is crucial for CPB preparation.…”
Section: Introductionmentioning
confidence: 99%